STUDIES ON TOXICOLOGICAL AND NEUROBEHAVIORAL PROFILE OF METHANOL EXTRACT OF MUSSAENDA ROXBURGHII HOOK. F. LEAVES IN MICE - SANJIT NAMASUDRA; PANKAJ PHUKAN; MEENAKSHI BAWARI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of this study was to evaluate the toxicity of Mussaenda roxburghii with special reference to the nervous system. Methods: For the study, 15 mice were obtained from Pasteur Institute, Shillong. The mice were then divided into three groups containing five mice in each group. The groups were, namely Group I, Group II, and Group III; Group I mice received distilled water and acted as a control group, Group II mice received plant extract at a dose of 600 mg/kg body weight (BWT.), and Group III mice received plant extract at a dose of 800 mg/kg BWT. The doses were administered orally through oral gavage tube for 28 days and the BWT of the mice was measured at 7th, 14th, 21th, and 28th days. The behavior of mice was evaluated for anxiety, locomotion, immobility, learning, and memory with the elevated plus maze test (EPMT), open field test (OFT), forced swim test (FST), and Morris water maze test (MWMT), respectively. Results: The result of the experiment showed a decrease in the BWT of mice exposed to plant extracts significantly as compared to the control. In the OFT, there is a significant decrease in total distance travel in OFT and also total distance travel in the central zone in mice treated with the plant extracts as compared to the control mice. In the EPMT, the plant extract treated mice showed a decreased in the time spent in open arms. The FST results in increased immobility in mice exposed to plant extracts as compared to control. In the present study, MWMT results in an increased escape latency and path length and in decreased annulus crossovers in plant extract treated group as compared to control. Conclusion: The results of the present study suggest that the plant extract alters the behavior of the treated mice and possesses neurotoxic activity.